Strong ERG Positivity in Papillary Intralymphatic Angioendothelioma of the Testis of a 24-Year-Old Male: A Case Report - Anne M. Schultheis; Mareike Sandmann; Stefan Steurer (Case Reports in Pathology)
Papillary intralymphatic angioendothelioma is a rare, low-grade neoplasm of lymphatic channels that usually presents intradermally or subcutaneously. We report the case of a 24-year-old male presenting with an isolated intratesticular palpable mass and symptoms of testicular pain. Preoperative ultrasound examination showed an irregular, heterogeneous mass. Subsequent surgery and pathologic assessment revealed a papillary intralymphatic angioendothelioma (PILA), formerly known as Dabska tumor within the lymphatic spaces.